Decisional Privacy and the Rights of the Child. - Dimopoulos, Georgina ([Place of publication not identified] : Routledge, 2022)
Decisional privacy gives individuals the freedom to act and make decisions about how they live their lives, without unjustifiable interference from other individuals or the state. This book advances a theory of a child's right to decisional privacy. It draws on the framework of the United Nations Convention on the Rights of the Child and extends the work of respected children's rights scholars to address a significant gap in understanding the interconnections between privacy, family law and children's rights. It contextualises the theory through a case study: judicial proceedings concerning medical treatment for children experiencing gender dysphoria. This work argues that recognising a substantive right to decisional privacy for children requires procedural rights that facilitate children's meaningful participation in decision-making about their best interests. It also argues that, as courts have increasingly encroached upon decision-making regarding children's medical treatment, they have denied the decisional privacy rights of transgender and gender diverse children. This book will benefit researchers, students, judicial officers and practitioners in various jurisdictions worldwide grappling with the tensions between children's rights, parental responsibilities and state duties in relation to children's best interests, and with the challenge of better enabling and listening to children's voices in decision-making processes.
AcknowledgementsList of abbreviations Note on referencing styleA child-friendly summaryIntroductionPART A: Privacy and Children's Rights: A Theoretical Perspective1. The meaning and value of privacy 2. A children's rights approach to decisional privacy3. Re-reading court judgments from a children's rights perspectivePART B: Children's Right to Decisional Privacy in Practice 4. Medical treatment for gender dysphoria as a 'special medical procedure'5. 'Harsh' but 'bound': re-reading the Full Court's judgment in Re Jamie6. The 'greatest advancement in transgender rights' for Australian children? Re-reading the Full Court's judgment in Re Kelvin7. Validating treatment that 'goes to the heart of an individual's identity': re-reading the Court of Appeal's judgment in Bell v Tavistock8. Recognising and respecting children's right to decisional privacy: conflicts, complexities and opportunitiesConclusion Index
Keywords: Children's rights; Autonomy; LAW / General; LAW / Child Advocacy; LAW / Civil Rights